Chitosan nanoparticles for sustained release of metformin and its derived synthetic biopolymer for bone regeneration - Chen, Ning-Xin; Su, Xiao-Lin; Feng, Yao; Liu, Qiong; Tan, Li; Yuan, Hui; Chen, Yun; Zhao, Jie; Zhao, Ya-Qiong; Dusenge, Marie Aimee; Hu, Jing; Ye, Qin; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Background: There are considerable socioeconomic costs associated with bone defects, making regenerative medicine an increasingly attractive option for treating them. Chitosan is a natural biopolymer; it is used in approaches for sustained slow release and osteogenesis, and metformin has osteoinductivity. Our study aimed to synthesize chitosan and human serum albumin (HSA) with a metformin nanoformulation to evaluate the therapeutic effects of this nanoformulation on bone defects in vitro. Methods: A pluripotent differentiation assay was performed in vitro on mouse bone marrow mesenchymal stem cells (BMSCs). Cell Counting Kit-8 was used to detect whether metformin was toxic to BMSCs. The osteogenesis-related gene expression of OCN and OPG from BMSCs was tested by real-time PCR. HSA, metformin hydrochloride, and chitosan mixtures were magnetically stirred to finish the assembly of metformin/HSA/chitosan nanoparticles (MHC NPs). The MHC NPs were characterized using transmission electron microscopy (TEM), dynamic light scattering (DLS), and Fourier transform infrared spectroscopy (FT-IR). To test the expression of OCN and OPG, western blot were used. MHC NPs were evaluated in vitro for their osteoinductivity using alkaline phosphatase (ALP). Results: BMSCs successfully differentiated into osteogenic and adipogenic lineages in vitro. According to real-time PCR, a 50 µM concentration of metformin promoted osteogenesis in BMSCs most effectively by upregulating the osteogenic markers OCN and OPG. The microstructure of MHC NPs was spherical with an average nanosize of 20 ± 4.7 nm and zeta potential of -8.3 mV. A blueshift and redshift were observed in MHC NPs following exposure to wavelengths of 1600~1900 and 2000~3700 nm, respectively. The encapsulation (%) of metformin was more than 90%. Drug release tests showed that MHC NPs have good stability and slow-release performance. Upon treatment with the studied MHC NPs for 3 days, ALP was significantly elevated in BMSCs. In addition, the MHC NPs-treated BMSCs upregulated the expression of OPG and OCN, as shown by real-time PCR and western blot. Conclusion: MHC NPs have a stable metformin release effect and osteogenic ability. Therefore, as a derived synthetic biopolymer, it is expected to play a role in bone tissue regeneration.